2020
DOI: 10.1038/s41467-020-18413-9
|View full text |Cite
|
Sign up to set email alerts
|

Protrudin and PDZD8 contribute to neuronal integrity by promoting lipid extraction required for endosome maturation

Abstract: Endosome maturation depends on membrane contact sites (MCSs) formed between endoplasmic reticulum (ER) and endolysosomes (LyLEs). The mechanism underlying lipid supply for this process and its pathophysiological relevance remains unclear, however. Here, we identify PDZD8—the mammalian ortholog of a yeast ERMES subunit—as a protein that interacts with protrudin, which is located at ER-LyLE MCSs. Protrudin and PDZD8 promote the formation of ER-LyLE MCSs, and PDZD8 shows the ability to extract various lipids from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
105
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 59 publications
(122 citation statements)
references
References 55 publications
12
105
1
Order By: Relevance
“…A differential proteomics analysis of brain extracts from wild-type and protrudin-deficient mice was performed to identify proteins that might function cooperatively with protrudin at ER-endosome MCSs. This analysis uncovered PDZD8, in addition to VAP-A and VAP-B, as a key binding partner of protrudin ( Elbaz-Alon et al, 2020 ; Shirane et al, 2020b ). An independent study also identified protrudin as a binding partner of PDZD8 ( Elbaz-Alon et al, 2020 ).…”
Section: The Protrudin-pdzd8 Complex At Er-endosome Mcssmentioning
confidence: 93%
See 4 more Smart Citations
“…A differential proteomics analysis of brain extracts from wild-type and protrudin-deficient mice was performed to identify proteins that might function cooperatively with protrudin at ER-endosome MCSs. This analysis uncovered PDZD8, in addition to VAP-A and VAP-B, as a key binding partner of protrudin ( Elbaz-Alon et al, 2020 ; Shirane et al, 2020b ). An independent study also identified protrudin as a binding partner of PDZD8 ( Elbaz-Alon et al, 2020 ).…”
Section: The Protrudin-pdzd8 Complex At Er-endosome Mcssmentioning
confidence: 93%
“…Neurons with HSP-associated mutations of the genes for spastin or REEP1 were recently found to manifest abnormal enlargement of LEs and lysosomal dysfunction as a result of defects in ER-endosome MCSs and impaired endosomal homeostasis ( Allison et al, 2017 ; Lee et al, 2020 ). As described in more detail below, disruption of the protrudin-PDZD8 complex has also been shown to result in the formation of abnormal LEs as well as in disturbance of neuronal polarity and axonal degeneration ( Shirane et al, 2020b ). These findings implicate the protrudin-PDZD8 complex in regulation of endosome maturation at ER-endosome MCSs.…”
Section: Relation Of Er-endosome Mcss To the Mechanism Of Axonopathymentioning
confidence: 99%
See 3 more Smart Citations